Development of Teacher Guide Book Based on Technological Pedagogical Content Knowledge (TPACK) on the Material of Forms of Matter and Their Changes for Grade IV Elementary School - Noni Lestari; Irdalisa; Nurrohmatul Amaliyah (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a teacher's guidebook based on Technological Pedagogical Content Knowledge, especially on the material of the state of matter and its changes in grade IV Elementary School. The method used in this study is the Research and Development research method through the Analysis, Design, Development, Implementation, and Evaluation approach. The level of feasibility and practicality and effectiveness through the stages of analysis, design, development, implementation, and evaluation that focus on the material of the state of matter and its changes are based on the trial of the feasibility and practicality of the product with respondents in the implementation, namely expert validation tests, teacher response questionnaires and students. The level of effectiveness measured through a simple evaluation in measuring the achievement of student learning motivation is based on a statistical test stating the rtable value in this study where N = 32 and sig. 0.05 of 0.349. From the results of the validity test in the table above, it is known that the feasibility variable has a calculated rvalue > rtable, so it can be said that all statement items in the feasibility variable are valid and can be used as a measuring tool in research. The results of the pretest and posttest analysis conducted to measure the improvement in student learning outcomes through the N-Gain test showed that the percentage of students who completed the product implementation group was 86.88%.